Corruption Scandals In Women's Path to Executive Power - Mitra, Sutapa (Université d'Ottawa / University of Ottawa, 2021)
This paper explores the relationship between corruption scandals and women’s path to executive power using the following research question: How do corruption scandals impact women’s path to executive power? This examination contributes to the literature on women executives, corruption and gender. I will trace women’s path to executive power and the impact of corruption scandal at different stages of their rise to national office using three case studies: Angela Merkel, Michelle Bachelet, and Ellen Johnson-Sirleaf. I will explore the impact of corruption scandals on their respective paths to national executive power using Beckwith’s removal and deferral framework. The findings showcase that corruption scandals can be beneficial to women’s rise to executive power in party leadership contests in parliamentary systems, and during national elections if corruption is a salient electoral topic and cultural gendered beliefs frame women candidates as less corrupt. For Merkel, corruption scandal was significant in accessing party leadership. For Johnson-Sirleaf, corruption scandal was significant during national elections. For Bachelet, corruption scandal had an ambiguous effect. Nevertheless, Bachelet’s case informs a theoretical contribution by demonstrating that deferral can occur without removal and still facilitate senior women’s path to power under Beckwith’s framework.
Keywords: Women executives; Women head of government; Corruption scandal; Women’s path to national leadership